SUCCESS IN MASTERING A FOREIGN LANGUAGE IN A MODERN NON-LINGUISTIC UNIVERSITY - Khatamov Ildar Urakovich (Western European Studies, 2024)
The article considers that the limited number of hours allocated to the study of foreign languages, the small “density” of classroom lessons, i.e. significant intervals between them, the low level of training in a foreign language, with which a certain number of students enter a non-linguistic university. But, nevertheless, the learning conditions are hardly so bad that it is impossible to obtain at least minimal, but practically significant results in the effectiveness of learning a foreign language.
Keywords: To foreign language communication; theoretical analysis; lifetime education